Solar Irradiance Variability Monitor for the Galileo Solar Space Telescope Mission: Concept and Challenges - Carlesso, Franciele; Rodríguez Gómez‬, Jenny Marcela; Barbosa, Adriany Rodrigues; Antunes Vieira, Luis Eduardo; Dal Lago, Alisson (Frontiers in Physics, 2022)
Long and reliable total solar irradiance (TSI) time series is one of the essential parameters for understanding solar contributions to climate change. The minor fluctuations of TSI in long timescales could impact the energy balance. Despite the improvement of accurate measurements provided by the instruments, at the time, long-term TSI variability and its effects had not been established. The space-borne radiometer era provided observations in short timescales from minutes to years. Therefore, this study presents an overview of irradiance observations, highlighting the importance of following its variability in different time scales. In this context, the Galileo Solar Space Telescope that has been developed by the Institute for Space Research (INPE), Brazil, includes the Irradiance Monitor Module with a radiometer cavity like the classical design and a next-generation compact radiometer.